2021
DOI: 10.1002/lary.29405
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing and Quality of Life in Adults With Chronic Rhinosinusitis

Abstract: Objectives/Hypothesis Psychological comorbidity is common in patients with chronic rhinosinusitis (CRS) and is correlated with decreased overall and disease‐specific quality of life (QoL). Prior research reported that anxiety and depression, as measured by the hospital anxiety and depression scale (HADS), are associated with worse CRS‐specific QoL, as assessed via the Rhinosinusitis Disability Index (RSDI). Furthermore, patients prone to anxiety/depression may display an exaggerated response to real or anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Pain catastrophizing also has a significant indirect relationship with quality of life through pain self-efficacy mediation (B =− 0.015). Therefore the results of the present study with the research of Alvarez-Astorga et al [ 39 ]; Sewell et al [ 33 ]; McPack et al [ 58 ]; De Carlo et al [ 57 ]; Hayashi et al [ 87 ]; Galvez Sanchez et al [ 88 ]; Kazi et al are consistent [ 56 ] And all have reported significant inverse relationships between pain catastrophizing and quality of life. In explaining these findings, it can be said that pain perception is a complex phenomenon and has cognitive, emotional, behavioral and motivational dimensions that affect each person differently [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pain catastrophizing also has a significant indirect relationship with quality of life through pain self-efficacy mediation (B =− 0.015). Therefore the results of the present study with the research of Alvarez-Astorga et al [ 39 ]; Sewell et al [ 33 ]; McPack et al [ 58 ]; De Carlo et al [ 57 ]; Hayashi et al [ 87 ]; Galvez Sanchez et al [ 88 ]; Kazi et al are consistent [ 56 ] And all have reported significant inverse relationships between pain catastrophizing and quality of life. In explaining these findings, it can be said that pain perception is a complex phenomenon and has cognitive, emotional, behavioral and motivational dimensions that affect each person differently [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…According to the research of Alvarez-Astorga et al [ 39 ] pain catastrophizing increases the symptoms of migraine in patients. Based on studies conducted by Kazi et al [ 56 ] in patients with Chronic rhinosinusitis; De Carlo et al [ 57 ] in young patients with Inflammatory bowel disease; Sewell et al [ 33 ] in chronic illnesses; MackPeak et al [ 58 ] in women with endometriosis; pain catastrophizing is associated with higher levels of pain that reduced quality of life. Research by Kalapurakkel et al [ 45 ] showed that higher levels of pain self-efficacy are recognized as a protective psychological resource in patients experiencing chronic pain and are associated with better performance.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CRS experience elevated rates of depression and anxiety with associated pain and pain catastrophizing, which has been associated with reduced quality of life. 23,24,28,29 Indeed, patients with CRS are 1.5 times more likely to develop depression and anxiety than those without CRS. 24 In this study population, we see almost 50% of patients reporting problems in the anxiety/ depression domain with sustained reductions in anxiety/ depression through five years after ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CRS experience elevated rates of depression and anxiety with associated pain and pain catastrophizing, which has been associated with reduced quality of life 23,24,28,29 . Indeed, patients with CRS are 1.5 times more likely to develop depression and anxiety than those without CRS 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of maxillary sinusitis include nasal congestion, nasal discharge, facial pain, rhinocnesmus, etc., [ 11 , 12 ]. Acute maxillary sinusitis can lead to life-threatening complications while chronic disease can seriously affect quality of life because of recurrent episodes and related discomfort [ 13 , 14 , 15 ]. Decreasing the incidence of maxillary sinusitis has become a goal of facial fracture management.…”
Section: Introductionmentioning
confidence: 99%